Pravna fakulteta Univerze v Ljubljani že kar 30. na svetu - Koritnik, Boštjan (Javna uprava, 2023)
In the 2022 Moot Court competitions, the Faculty of Law at the University of Ljubljana achieved an exceptional ranking on the Nica.team performance scale: 1st in Slovenia, 13th in Europe, and an impressive 30th globally. This result marks a notable improvement from 2021 when our esteemed faculty secured the 43rd position worldwide, itself a testament to our excellence in these student-led competitions. Moot Court competitions serve as simulations of court and arbitration proceedings, with students stepping into the roles of dispute parties’ delegates. The competitions, typically conducted in English or French, require students to address timely legal and social issues across a broad spectrum of law fields. These include European Union law, international commercial law, human rights law, criminal law, asylum law, and space law, among others.
Keywords: competition; moot court; Nica.team; Nice.team; Pravna fakulteta Univerze v Ljubljani; simulacija; simulation; students; študenti; tekmovanja; University of Ljubljana Faculty of Law